Cryogenic liquid jets for high repetition rate discovery science - Curry, Chandra B.; Schönwälder, Christopher; Goede, Sebastian; Kim, Jongjin B.; Rehwald, Martin; Treffert, Franziska; Zeil, Karl; Glenzer, Siegfried H.; Gauthier, Maxence (Journal of Visualized Experiments, 2020)
This protocol presents a detailed procedure for the operation of continuous, micron-sized cryogenic cylindrical and planar liquid jets. When operated as described here, the jet exhibits high laminarity and stability for centimeters. Successful operation of a cryogenic liquid jet in the Rayleigh regime requires a basic understanding of fluid dynamics and thermodynamics at cryogenic temperatures. Theoretical calculations and typical empirical values are provided as a guide to design a comparable system. This report identifies the importance of both cleanliness during cryogenic source assembly and stability of the cryogenic source temperature once liquefied. The system can be used for high repetition rate laser-driven proton acceleration, with an envisioned application in proton therapy. Other applications include laboratory astrophysics, materials science, and next-generation particle accelerators.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Cryogenic liquids; Engineering; Fluid dynamics; High repetition rate; Issue 159; Laser-driven ion acceleration; Liquid jets